FC 090EFFECTS OF FINERENONE ON CARDIORENAL OUTCOMES IN BLOOD PRESSURE SUBGROUPS IN PATIENTS WITH CKD AND T2D. (29th May 2021) - Ruilope, Luis; Agarwal, Rajiv; Anker, Stefan D; Filippatos, Gerasimos; Pitt, Bertram; Rossing, Peter; Sarafidis, Pantelis; Schmieder, Roland E; Joseph, Amer; Mentenich, Nicole; Nowack, Christina; Bakris, George
Abstract: Background and Aims: Finerenone is a novel, selective, nonsteroidal mineralocorticoid receptor antagonist (MRA) that significantly reduced the risk of adverse kidney and cardiovascular (CV) outcomes in patients with chronic kidney disease (CKD) and type 2 diabetes (T2D) in the FIDELIO-DKD trial. In phase II studies, finerenone had modest effects on office blood pressure (BP) compared with the steroidal MRA spironolactone. We report an analysis of the relationship between baseline and changes in office systolic BP (SBP) and outcomes with finerenone in the FIDELIO-DKD trial. Method: In FIDELIO-DKD, 5734 patients were randomised 1:1 to oral finerenone or placebo. Patients with T2D, urine albumin-to-creatine ratio (UACR) ≥30–<300 mg/g, estimated glomerular filtration rate (eGFR) ≥25–<60 ml/min/1.73 m2 and a history of diabetic retinopathy, or UACR ≥300–≤5000 mg/g and eGFR ≥25–<75 ml/min/1.73 m2, and treated with optimised renin–angiotensin system blockade were eligible. The primary endpoint was time to kidney failure, sustained eGFR decline ≥40% from baseline, or renal death. The key secondary endpoint was time to CV death, non-fatal myocardial infarction, non-fatal stroke, or hospitalisation for heart failure. A Cox proportional hazards model was used to investigate the relationship between treatments and efficacy outcomes adjusted for baseline SBP and change in SBP from baseline to month 4. Results: A total of 5669 patients with available baseline SBP data were analysed. At baseline, the mean SBP and diastolic BP were 138.0 and 75.8 mmHg, respectively. Patients treated for hypertension at baseline received an average of 3.3 antihypertensive therapies. The study population was stratified by quartiles (Q) of SBP at baseline: ≤128.7 mmHg (Q1); >128.7–≤138.3 mmHg (Q2); >138.3–≤148.0 mmHg (Q3); and >148.0 mmHg (Q4). Patients in higher SBP categories tended to be older, with higher median UACR, but similar mean eGFR at baseline. Effects of finerenone, estimated as hazard ratios (HRs), were consistent across the quartiles for the primary endpoint (HR [95% CI]: Q1, 0.87 [0.66–1.15]; Q2, 0.76 [0.59–0.98]; Q3, 0.81 [0.65–1.02]; Q4, 0.86 [0.70–1.07]; p-value for interaction=0.87) and the key secondary endpoint (HR [95% CI]: Q1, 0.95 [0.69–1.29]; Q2, 0.81 [0.60–1.10]; Q3, 0.79 [0.60–1.03]; Q4, 0.91 [0.70–1.18]; p-value for interaction=0.78) (Figure ). Finerenone treatment resulted in a modest reduction in SBP; over the duration of the trial, overall mean difference in SBP between treatment groups was –2.7 mmHg. Maximum differences in SBP between finerenone and placebo were observed at month 4; the mean change in SBP from baseline to month 4 across SBP quartiles were: Q1: 4.99 and 9.01 mmHg; Q2: –0.85 and 2.43 mmHg; Q3: –5.63 and –2.40 mmHg; Q4: –11.76 and –6.44 mmHg, for finerenone and placebo, respectively. Adjusting for baseline SBP and SBP change to month 4 resulted in small changes in treatment effect for the primary endpoint and the key secondary endpoint, with only slightly increased HRs for treatment compared with the unadjusted primary analysis (primary endpoint: HR: 0.85 vs 0.82; key secondary endpoint: HR: 0.90 vs 0.86) and no strong indication of an interaction between treatment and SBP. Conclusion: In FIDELIO-DKD, a small proportion of the effect of finerenone on cardiorenal outcomes can be attributed to BP. However, most of the effect appears to be via BP-independent mechanisms. (Funded by Bayer AG; FIDELIO-DKD ClinicalTrials.gov number, NCT02540993)